1999
DOI: 10.1074/jbc.274.37.26431
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Stimulation of Human Insulin-like Growth Factor-binding Protein-5 Gene Transcription in Human Osteoblasts Is Mediated by a CACCC Sequence in the Proximal Promoter

Abstract: Insulin-like growth factor-binding protein-5 (IGFBP-5)is produced by osteoblasts and potentiates insulin-like growth factor mitogenic stimulation in osteoblast cell cultures. Progesterone (PG) increased IGFBP-5 expression in normal human osteoblasts and increased IGFBP-5 transcription in U2 human osteosarcoma cells. We developed a chloramphenicol acetyltransferase reporter construct containing the human IGFBP-5 proximal promoter sequence, which includes TATA and CAAT boxes, and five putative PG response elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 79 publications
0
26
1
Order By: Relevance
“…When both elements were deleted, promoter activity was almost completely abolished. In the literature, the CA-rich element is described as a PR-sensitive element (Boonyaratanakornkit et al 1999). A mutant used by the authors of this article in which 3 Cs were exchanged with As was no longer able to confer PR activity to the IGFBP5 promoter.…”
Section: Coordinated Expression Of Mn1 and Igfbp5 In Meningiomasmentioning
confidence: 99%
See 3 more Smart Citations
“…When both elements were deleted, promoter activity was almost completely abolished. In the literature, the CA-rich element is described as a PR-sensitive element (Boonyaratanakornkit et al 1999). A mutant used by the authors of this article in which 3 Cs were exchanged with As was no longer able to confer PR activity to the IGFBP5 promoter.…”
Section: Coordinated Expression Of Mn1 and Igfbp5 In Meningiomasmentioning
confidence: 99%
“…The progesterone receptor (PR) does not stimulate the IGFBP5 promoter in Hep3B cells and U2 osteosarcoma cells (U2OS) cells, and the effect of MN1 is not affected by PR It has previously been shown by Boonyaratanakornkit et al (1999) that the PR can stimulate the IGFBP5 promoter in the presence of its ligand, progesterone. Although no canonical PR-responsive elements are present in the IGFBP5 promoter, Boonyaratanakornkit et al (1999) showed that induction by PR is mediated by the CACCC element in the promoter.…”
Section: Mn1 Binds Indirectly To Ca-containing Oligonucleotidesmentioning
confidence: 99%
See 2 more Smart Citations
“…In human bone and BM, IGFBP5 is expressed in chondrocytes, osteoblasts and osteocytes. These cell types express androgen receptors [26][27][28][29], however only androgen regulation of IGFBP 2, 3, 4 and not of IGFBP5 has been examined in-vitro [30].…”
Section: Introductionmentioning
confidence: 99%